2018
DOI: 10.4314/thrb.v20i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative pain prevalence, predictors, management practices and satisfaction among operated cases at a Regional Referral Hospital in Dar es Salaam, Tanzania

Abstract: Background: Post-operative pain is an essential component of good surgical patient care plan. In developing countries however, the prevalence of post-operative pain is relatively very high and pain control strategies are not very promising. The objective of this study was to assess post-operative pain prevalence, predictors, management practices and satisfaction among operated cases at a regional referral hospital in Dar es Salaam, Tanzania.Methods: Prospective hospital based descriptive observational study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
3
5
3
Order By: Relevance
“…Patients who underwent general surgery and urology 3.602 times (AOR=3.602, CI: 1.107–11.727) more likely to report moderate to severe pain than patient who underwent gynecologic procedure. This finding was against the study in Tanzania in which orthopedic procedures were found to be associated with moderate to severe pain (AOR=3.456, P =0.05)36. The possible explanation for this variation was the majority of orthopedics cases in our study had regional anesthesia for their POPM.…”
Section: Discussioncontrasting
confidence: 83%
“…Patients who underwent general surgery and urology 3.602 times (AOR=3.602, CI: 1.107–11.727) more likely to report moderate to severe pain than patient who underwent gynecologic procedure. This finding was against the study in Tanzania in which orthopedic procedures were found to be associated with moderate to severe pain (AOR=3.456, P =0.05)36. The possible explanation for this variation was the majority of orthopedics cases in our study had regional anesthesia for their POPM.…”
Section: Discussioncontrasting
confidence: 83%
“…It might be due to the different time's initial visit of patients [ 33 ]. The scheduling of evaluation of the patients postoperatively stated by the majority of the studies was different from our study, the majority of the studies showed that the first assessment was done at 12 h 24 h, and 48 h postoperatively [ 36 , 37 ]. While our study first assessed the patient at 2 h, postoperatively, this could also explain the differences between the results.…”
Section: Discussioncontrasting
confidence: 58%
“…Globally the prevalence of POP differs among studies. For instance, the American Pain Society suggests a prevalence of more than 80% with 75% reporting moderate to severe pain [4]. Studies in Sub-Saharan Africa reveal that POP has been undertreated and the burden of POP ranges from 40 to 95% [5,6].…”
Section: Introductionmentioning
confidence: 99%